Acculturation, belongingness and identity for migrants in Germany.
EU-funded researchers investigated migrant, host and intergenerational perspectives on psychological and sociocultural adaptation of migrants and on attitudes about integration, feelings of belongingness and group affiliation. Their work included development of a theoretical framework addressing the bidirectional nature of the acculturation process.